Herramienta Canva para mejorar el nivel de logro en el área de Ciencias Sociales en estudiantes de educación secundaria - Anticona Ganoza, Italo Junior (2023)
The purpose of this research was to determine if the use of the Canva tool significantly improves the level of achievement in the area of Social Sciences of 2nd graders at 80819 - Francisco Lizarzaburu - High School in Trujillo, 2021. It was an applied research of quantitative approach, longitudinal-experimental design, quasi-experimental level and of hypothetical-deductive method, which was carried out on a population of 77 students with a non-probability selected sample of 30 students for the control group and a sample of 20 students for the experimental group, and to whom a 12-item instrument was applied using the Likert Scale. In the hypothesis testing, the SPSS 22 statistical software was used to analyze the data and the student's t-test to contrast the hypothesis, which determined that there are significant differences in the p-value given by the bilateral significance = 0,000 < 0.05 m as well as t = 9.75. The descriptive results showed differences in the learning levels between the experimental group and the control group, since 100 % of students of the experimental group obtained process, expected and outstanding levels, while 43.3 % of students of the control group remained in the starting level. This was confirmed by the difference testing.